AKTIVITAS ANTIBAKTERI DARI SEDIAAN GEL EKSTRAK TERPURIFIKASI KELOPAK ROSELLA TERHADAP BAKTERI Escherichia coli - Fita Sari; Ida Kristianingsih; Tri Puji Lestari; Fathul Hidayatul; Yuyun Wulandari (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2023)
Natural materials had various types of primary and secondary metabolite compounds that were useful for treating a disease. Plant materials that contain high levels of secondary metabolites could be developed into raw materials for traditional medicines. An example of the development of natural medicine which was in high demand is making traditional medicinal raw materials which have antibacterial properties. These could add to the type of therapy for a disease with smaller side effects. The aim of this study was to determine the activity of the purified extract gel preparation of rosella petals as an antibacterial. The extract was obtained from the maceration method which was then followed by purification. The antibacterial activity test in this study used the well diffusion method. Detection of metabolites by Thin Layer Chromatography (TLC) includes the stationary phase of silica GF254 and the mobile phase Toluene: Acetic acid: Formic acid (6:6:1). The concentration of purified extract of rosella petals for the formulation was 5, 15 and 25%. Data analysis was carried out with the One Way Anova test with a 95% confidence level. The results of the research that the purified extract gel preparation of rosella petals has the potential to inhibit the growth of Escherichia coli bacteria in the sensitive category at a concentration of 25%. The results of a positive phytochemical screening for flavonoid compounds were indicated by the formation of a red-orange color in the test and identification using TLC produced an Rf of 0.85 which has similarities with previous studies. The conclusion of this study was that the ETKR gel preparation with a concentration of 25% was sensitive as an antibacterial